When molecular biology transforms clinical oncology: the EGFR journey in colorectal cancer - Pietro Paolo Vitiello; Nadia Saoudi González; Alberto Bardelli (Molecular Oncology)
The discovery of growth factors and their involvement in cancer represents the foundation of precision oncology. The preclinical and clinical development of agents targeting epidermal growth factor receptor (EGFR) in colorectal cancer (CRC) were accompanied by big hype and hopes, though the clinical testing of such agents clashed with intrinsic and acquired resistance, greatly limiting their therapeutic value. However, a better understanding of the biology of the EGFR signaling pathway in CRC, coupled with the development of liquid biopsy methodologies to study cancer evolution in real time, fostered the clinical refinement of anti‐EGFR treatment in CRC. Such a workflow, based on the co‐evolution of biology knowledge and clinical development, allowed to couple the discovery of relevant therapy resistance mechanisms to the development of strategies to bypass this resistance. A broader application of this paradigm could prove successful and create an effective shortcut between the bench and the bedside for treatment strategies other than targeted therapy.